Rotavirus Binding to Cell Surface Receptors Directly Recruiting α2 Integrin. Issue 12 (11th August 2021) - Yang, Jinsung; Park, Jeongsoo; Koehler, Melanie; Simpson, Joshua; Luque, Daniel; Rodríguez, Javier M.; Alsteens, David
Abstract : Rotavirus interactions with endogenous cell surface receptors are of fundamental interest in virology and medicine; however, the evidence of rotavirus directly binding to the receptors and the consequent dynamic behaviors are still elusive. Force–distance curve‐based atomic force microscopy allows for the extraction of biophysical properties underlying binding of single virions to receptors and clarification of the dynamics of rotavirus–receptor interactions. Unfortunately, this method is time‐consuming due to the lack of automation when analyzing large data sets. Herein, rotavirus–receptor interactions and early endocytosis behaviors using automated high‐throughput analysis are examined. It is demonstrated that rotavirus binds to α‐linked sialic acid and α2 β1 integrin. The effect of trypsinization is investigated on the capsid protein VP4 binding to the receptors. Using fluidic force microscopy, it is demonstrated that the interaction leads to α2 integrin recruitment to the cell‐bound rotavirus on the plasma membrane. Further, it is illustrated that an integrin‐derived peptide can impede binding and alter downstream dynamics. Taken together, these results open a new understanding of the infection mechanism of rotavirus and suggest a novel inhibitory peptide against rotavirus binding. Abstract : Rotavirus receptor binding is characterized using atomic force microscopy (AFM). It is demonstrated that altering mechanical properties through trypsinization of rotavirus impacts binding to sialic acid and α2 β1 integrins and subsequent recruitment of α2 integrins to the binding site. This novel approach opens new avenues for finding antiviral molecules.